Pseudophlugiolopsis bitubera gen. nov., sp. nov. and a new species of Allicyrtaspis Shi, Bian & Chang, 2013 (Tettigoniidae: Meconematinae: Meconematini) from China - Wang, Tao; Zhou, Zhijun; Chang, Yanlin (Zootaxa, 2020)
A new genus is proposed for Pseudophlugiolopsis bitubera gen. nov., sp. nov. from Yunnan, China. Another new species of the genus Allicyrtaspis is described: Allicyrtaspis? phryganis sp. nov. The type specimens are preserved in the Museum of Hebei University.